Surplus Extraction and Competition - Peters, Michael (Review of Economic Studies, 2001)
A competitive economy is studied in which sellers offer alternative direct mechanisms to buyers who have correlated private information about their valuations. In contrast to the monopoly case where sellers charge entry fees and extract all buyers' surplus, it is shown that in the unique symmetric equilibrium with competition, sellers hold second price auctions with reserve prices set equal to their cost. Most important, it is a best reply for sellers not to charge entry fees of the kind normally used to extract surplus, even though it is feasible for them to do so.